Taper fretting corrosion with Stryker Anato stem after hip replacement - Freccero, David M. (Arthroplast Today, 2020)
We report a case of head-neck taper fretting corrosion in a patient who had a total hip replacement with a noncemented Stryker Anato femoral stem and a V40 metal head with a Stryker Tritanium hemispherical socket with a highly cross-linked polyethylene liner (metal on polyethylene) (Stryker, Mahwah, NJ, USA). A 57-year-old man presented with early-onset hip pain after right total hip arthroplasty. Workup was negative for infection. Metal artifact reduction sequence MRI revealed an encapsulated fluid mass. Metal ion cobalt level was elevated at 6 ppb. The patient underwent right revision total hip arthroplasty with excellent results at 1-year follow-up.